Application of clown care in hospitalized children: A scoping review. - Guo Xin; Fu Yingping; Chen Yue; Wu Jiaming; Hu Xue (PLoS ONE)
Purpose This study aims to provide healthcare providers with insights into relevant interventions by examining the timing, format, content, outcome measures, and effects of clown care interventions on hospitalized children. Methods This study utilized a scoping review methodology based on the framework by Arksey and O'Malley. The search for Chinese and English literature on the utilization of clown care for hospitalized children was conducted in databases including CNKI, VIP, Wanfang, China Biology Medicine Database, PubMed, Embase, Web of Science, CINAHL, and Cochrane Library. At the same time, the references and other grey literatures included in the paper were also manually searched. covering publications from inception to December 10, 2023. Screening of the literature was done based on predefined inclusion and exclusion criteria, with data extraction and synthesis carried out independently by two researchers. Results Out of 1084 articles screened, 18 were included. Clown care can be used with children who have burns, perioperative care, fracture rehabilitation, autism, puncture therapy, chemotherapy, respiratory pathologies and disabled children, according to a review of the literature. Clown care is feasible and available for these kids, and it has been shown to have favorable impacts. The main interventions used in clown care are guided imagery, cognitive coping, emotional reflection, distraction, and empowerment. Physical(reduced children's pain levels), psychological(reduced anxiety, improved coping skills, quicker recovery), cognitive-behavioral(for example, the number of meaningful words that children with autism say in 10 minutes.), and other indications are the several types of clown care outcome indicators. Conclusions Clown care can lessen a hospitalized child's pain, alleviate their worry, and divert their focus from illness and suffering. However, not all pediatric patients benefit from clown care. Every youngster is an independent individual with unique personality traits, and some may experience intense pain along with a terror of the clown role. Future research should concentrate on understanding the characteristics of hospitalized children to develop tailored clown care programs that can enhance clinical effectiveness. Trial registration number https://doi.org/10.17605/OSF.IO/B4KMV.